A Novel Way to Study Human Hereditary Diseases: Modeling Large-Scale (CAG) Expansions in Yeast. - Harris, Samantha T. (Tufts Archival Research Center, 2014)
Abstract: Approximately 30 human hereditary diseases have been linked to large-scale expansions of repetitive microsatellites, such as the (CAG)n trinucleotide repeat. Discovering how these repeats are expanding is central to the understanding of the disease progression in human pedigrees. While previous work with (GAA)n repeats has shed light on how these large-scale expansions are occurring, this work has yet to be expanded to include (CAG)¬n repeat expansions. In order to unravel this mechanism, we used a budding yeast model system in which (CAG)140 repeats were artificially integrated into two different cassettes to allow for recovery of large-scale expansions. Upon creating the cassettes, we were able to knock out both the Srs2 and Tof1 proteins to see their effect on repeat expansions. Additionally, we conducted a transposon mutagenesis screen to uncover genes involved in large-scale repeat expansions. Our work with these mutant yeast strains has provided us with evidence of the difference between (CAG)n repeat expansions and other trinucleotide repeats, supporting the balancing hypothesis of repeat expansions.